Assessment of cytology and mucin 2 in colorectal mucus collected from patients with inflammatory bowel disease: Results of a pilot trial. Issue 2 (28th January 2016) - Loktionov, Alexandre; Chhaya, Vivek; Bandaletova, Tatiana; Poullis, Andrew
Abstract: Background and Aim: Non‐invasive diagnosis of colorectal disease remains problematic, fecal biomarkers presenting the only current option. Colorectal mucus is the diagnostically informative element of stool samples, but its separation from stool is difficult. We aimed to: (i) test a novel method of non‐invasive colorectal mucus sampling in a pilot clinical trial; (ii) evaluate sampling method acceptance by study participants; (iii) characterize the collected material cytologically; and (iv) assess feasibility of quantitative protein analysis in the samples. Methods: A total of 141 patients with IBD (58), IBS (50), and healthy controls (33) participated in the study. Samples rich in colorectal mucus were self‐collected by swabbing the anal area immediately following defecation. Collected samples were examined cytologically and subjected to quantitative analysis for total protein and mucin 2 (MUC2). Results: The novel sampling technique was assessed as "good" or "adequate" by 96% of study participants. A total of 55% of the collected samples were free of fecal contamination. Cytology showed large numbers of well preserved inflammatory cells in IBD cases. Total protein values varied in all groups, being affected by fecal contamination. MUC2 levels were similar among all IBD‐free individuals (control and IBS groups) and elevated in IBD patients ( p  < 0.001). MUC2 measurement applied as a test for IBD detection provided sensitivity = 72.4% and specificity = 86.7%. Conclusions: A novel non‐invasive method for collecting human colorectal mucus has been successfully tested. The method was very well accepted by trial participants. The results have proven high quality of collected samples for both cytological investigation and diagnostic biomarker analysis.